2010
DOI: 10.1002/hep.23485
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of survival rates of untreated patients in randomized clinical trials of hepatocellular carcinoma†

Abstract: Knowing the spontaneous outcome of hepatocellular carcinoma (HCC) is important for designing randomized controlled trials (RCTs) of new therapeutic approaches; however, survival of patients in the absence of treatment is highly variable, and prognostic factors influencing outcomes are incompletely defined. The aims of this meta-analysis were to estimate the 1-year and 2-year survival rates of untreated HCC patients enrolled in RCTs of palliative treatments, and to identify prognostic factors. RCTs evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
337
7
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(358 citation statements)
references
References 43 publications
7
337
7
7
Order By: Relevance
“…To calculate the transition probabilities, all values of average annual transition probabilities for one year-cycle length were changed to semi-annual probabilities by the survival curve function and put into six month-cycle length estimation. Transition probabilities were obtained from published studies (Lee et al, 2002;Chung, 2005;Yeung et al, 2005;Chen et al, 2006;2009;Fattovich et al, 2008;Bouza et al, 2009;Cheng et al, 2009;Kim et al, 2009;Cabibbo et al, 2010;Tong et al, 2010;Zhou et al, 2010a;2010b;Chun et al, 2011;Kao, et al, 2011;Sawhney et al, 2011;Thein et al, 2012).…”
Section: Transitional Probabilitiesmentioning
confidence: 99%
“…To calculate the transition probabilities, all values of average annual transition probabilities for one year-cycle length were changed to semi-annual probabilities by the survival curve function and put into six month-cycle length estimation. Transition probabilities were obtained from published studies (Lee et al, 2002;Chung, 2005;Yeung et al, 2005;Chen et al, 2006;2009;Fattovich et al, 2008;Bouza et al, 2009;Cheng et al, 2009;Kim et al, 2009;Cabibbo et al, 2010;Tong et al, 2010;Zhou et al, 2010a;2010b;Chun et al, 2011;Kao, et al, 2011;Sawhney et al, 2011;Thein et al, 2012).…”
Section: Transitional Probabilitiesmentioning
confidence: 99%
“…A meta-analysis of 30 clinical trials into which HCC patients were enrolled for palliative treatment reflects this heterogeneity. It demonstrated a high variability in survival among untreated patients and concluded that no single patient characteristic alone could predict outcome [2].The prognosis and treatment options for HCC are generally related to tumor stage and liver function at presentation [3,4]. In the west, approximately 30% of all patients with HCC are diagnosed in…”
mentioning
confidence: 99%
“…In our study, no cases with HCC rupture were found in A group, but 2 cases in B group, because usually OA was involved in the marginal part of the tumor, where part of rupture is often located, so chemoembolization via the POA may have potential effect for preventing HCC rupture. [22][23][24][25] . This is why we didn't perform statistical compassion of these patients' survival outcomes between A and B groups.…”
Section: Discussionmentioning
confidence: 99%